Thermal analysis and multi-objective optimization of equal-area microfluidic cooling systems - Yucheng Wang; Antong Bi; Yue Yao; Weiting Chen; Kaiyu Chen; Shenxin Yu; Jiangang Yu; Chao Wang; Wei Li; Shaoxi Wang (Results in Engineering, 2025)
Microfluidic cooling has demonstrated great potential in addressing the escalating thermal challenges of power electronic systems. However, most current structural designs do not take into account the constraint of a fixed heat transfer area, limiting the practical relevance and comparability of performance evaluations. This study investigates the effects of different microchannel geometries on cooling performance while maintaining a constant heat transfer area. Four distinct microchannel designs were selected to explore how variations in structure impact thermal management efficiency. Computational Fluid Dynamics (CFD) simulations were conducted to evaluate temperature distribution, pressure drop, Nusselt number, and thermal resistance as functions of flow velocity, and the performance evaluation criterion (PEC) was applied to comprehensively assess the overall performance of each design. The testing results showed that zigzag microchannels reduced convective thermal resistance by up to 10 % compared to the straight design. The double-period zigzag structure achieved the highest PEC. CFD simulations demonstrated good agreement with experimental data, with a maximum deviation of 3 %, validating the model's accuracy. Moreover, An orthogonal experimental design combined with a multi-objective optimization algorithm was applied to minimize both the average heat source temperature and pressure drop. The optimization achieved a 14.4 % reduction in pressure drop for the through-flow channels (MCC) and a 24.8 % reduction for the double-period zigzag channels (MC-D). The solution set offers flexibility in design selection based on specific priorities. This research provides a practical approach to microchannel design, offering insights that can inform thermal management strategies for high heat flux density chips.